The predictive effect of extrinsic motivation on English online learning engagement - Xu, Zhixin (Frontiers in Psychology, 2025)
This study investigates the predictive role of extrinsic motivation on online learning engagement among Chinese non-English-major undergraduates, framed within Self-Determination Theory (SDT). Through a questionnaire survey of 472 students in hybrid teaching environments, the research examines the interplay between extrinsic motivation subtypes (external, introjected, identified, and integrated regulation) and multidimensional online engagement (behavioral, cognitive, emotional, and social). Results reveal that extrinsic motivation is predominantly manifested through autonomous forms (identified and integrated regulation), while overall online engagement remains moderate, with social engagement lagging significantly. Correlation and structural equation modeling analyses demonstrate that all extrinsic motivation subtypes positively predict engagement, with introjected regulation (less autonomous) exhibiting the strongest predictive power. These findings validate the continuity of motivational regulation in SDT and highlight the context-specificity of extrinsic motivation’s effects, providing theoretical insights for understanding motivation-engagement dynamics and pedagogical implications for optimizing hybrid teaching policies and motivational strategies in global foreign language contexts.